Adaptasi Pola Ritme Dangdut pada Ansambel Perkusi - Agus Salim (Institut Seni Indonesia Yogyakarta, 2010)
Dangdut Rhythmic Pattern Adaptation on Percussion Ensamble. This article discuss the adaptation processof “Dangdut” rhythmic pattern and its tone qualities that were implemented in to the percussion ensemble. Earlierstudies showed that bath elements can pessibly be tone. It means that the differences between characteristic musicbasically can be used as a new musical idea to produce a new genre of music. This procedure began with theimplementation of new special symbol to be fi tted in to the western notation; it follows by the selection of “Dangdut”rhythmic pattern and to be implemented in to the percussion ensemble instruments such as timpani, bongo, hi-hat,roto-toms and tambourine. The result was a new color of musical genre that gives a new propective and possibilityin the world of music composition.